A review on interrelation among post-authorisation study, regulatory action and pharmacogenetics in pharmacovigilance - Nusrat, Tanzina (BRAC University, 2019)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2017.